2002
DOI: 10.2169/internalmedicine.41.993
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke-induced Acute Eosinophilic Pneumonia Accompanied with Neutrophilia in the Blood.

Abstract: Smoking causes various changes in the lung. This report describes a case of cigarette smoke-inducedacute eosinophilic pneumonia (CS-AEP) with neutrophilia in the blood. However, the precise mechanismis unknown,so we examined the effect of exposure to cigarette smokeextracts on the production of interleukin (IL)-4, IL-5, IL-8, IL-18, granulocyte macrophage-colony stimulating factor (GM-CSF), and vascular endothelial growth factor (VEGF) by human bronchial epithelial cells (HBECs) obtained from the patient. Wefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Steroid therapy is known to have a dramatic effect on the function of eosinophils in vitro (29) and in patients with AEP (1)(2)(3)(4)(5)(6)(7). As well, IL-8 secretion from respiratory epithelial cells is suppressed by dexamethasone (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Steroid therapy is known to have a dramatic effect on the function of eosinophils in vitro (29) and in patients with AEP (1)(2)(3)(4)(5)(6)(7). As well, IL-8 secretion from respiratory epithelial cells is suppressed by dexamethasone (23).…”
Section: Discussionmentioning
confidence: 99%
“…The collection and culture of HBECswere performed as previously described (6,8). Then, HBECs and BEAS-2B cells were exposed to cigarette smoke extract (CSE) as previously described (6).…”
Section: Effect Of Exposure To Cigarette Smoke On Humanbronchial Epitmentioning
confidence: 99%
See 1 more Smart Citation
“…Cigarette smoke activates macrophages and neutrophils to release proinflammatory mediators, chemokines and elastolytic enzymes [14]. CXC chemokine ligand (CXCL)8 is an important chemokine produced by macrophages, neutrophils and epithelial cells and induces the recruitment of neutrophils to the airways [15,16]. As a part of the innate immune response, pattern recognition receptors mediate the interaction between conserved patterns on micro-organisms and the host.…”
mentioning
confidence: 99%
“…1,2 Respiratory failure often develops in patients with AEP, but treatment with corticosteroids achieves an excellent response. 1,2 The etiology of AEP is unknown, but several studies [3][4][5][6][7][8][9] have proposed that cigarette smoke is potentially related to the onset of AEP. Philit et al 10 reviewed 22 patients with AEP, including 8 current smokers, and found that 6 of the 8 current smokers had started smoking within 3 months before the onset of AEP.…”
mentioning
confidence: 99%